Communication Channel Role in Micro-hydro Innovation Communication - Nugroho, Julian; Sumardjo; Anna Fatchiya; Dwi Retno Hapsari (Jurnal Public Relations (J-PR), 2025)
ABSTRACT This research was aimed to study the role of local innovator in communication activities of micro-hydro innovation adoption. Data was collected by using questionnaires in census principle to 99 household heads of the innovation adopter. The result showed that majority of the microhydro electricity adopters in Kedungrong, Blumbang, and Jarakan Villages were observing first the positive development before they finally adopted it. Majority of them adopted micro-hydro electricity at first 3 years since the local micro-hydro installations were built completely in their respective villages. Few other adopter family heads then followed adopting micro-hydro electricity at 4-6 years since the local micro-hydro installations were built completely in their respective villages. Eventually fewer other adopter family heads then followed adopting micro-hydro electricity at 7-10 years since the local micro-hydro installations were built completely in their respective villages. Majority of the respondents only used cellphone as communication channel with WhatsApp application in it to communicate between one and another.